IMPROVING READING COMPREHENSION OF THE ELEVENTH GRADE STUDENTS OF MA ALKHAIRAAT BIROMARU THROUGH STORY MAPPING STRATEGY - Marmumah; Mukrim, Mukrim; Maf'ulah, Maf’ulah; Darmawan, Darmawan (e-Journal of ELTS (English Language Teaching Society), 2024)
The reading comprehension of class X1 students at MA Alkhairaat Biromaru. This research uses a quasi-experimental design by applying a nonequivalent control group design. The population was class X1 students at MA Alkhairaat Biromaru consisting of 30 students from two classes. The sample is class IPA as the experimental group and class IPS as the control group. Sample selection was carried out in total. Tests are used to collect data consisting of pre-test and post-test. The test results show that the average pre-test score obtained by the experimental group is 40.47, while the mea pre-test score obtained by the control group is 43.53. Then, the average post-test score for the experimental group is 86.68, while the control group is 67.13; the t-calculated value (4.28) was higher than the t-table value (1.70), which means that the hypothesis was accepted. The T-test tests determine the significance and relevance between two groups of unpaired samples. Based on the research results, using Story Mapping can improve the reading comprehension of class X1 students at MA Alkhairaat Biromaru.